Touch, feel, heal. The use of hospital green spaces and landscape as sensory-therapeutic gardens: a case study in a university clinic - Dinu Roman Szabo, Mihaela; Dumitras, Adelina; Mircea, Diana-Maria; Doroftei, Dana; Sestras, Paul; Boscaiu, Monica; Brzuszek, Robert F.; Sestras, Adriana F. (Frontiers in Psychology, 2023)
It has been documented that patients with mental or physical disabilities can benefit from being placed within the setting of a natural environment. Consequently, the concept of creating spaces that can enhance health preservation or patient recovery, while also augmenting environmental and aesthetic value, has merged as a contemporary discourse. Green areas around hospitals can offer a great opportunity to incorporate healing gardens to benefit their patients and not only. The aim of this paper is to propose a design for a sensory-therapeutic garden based on key principles derived from selected academic literature, focusing on the application of these principles in a healthcare setting in Cluj-Napoca, Romania. The design was informed also by onsite data collection and analysis, and it aims to create a healing landscape that addresses the needs of patients, healthcare providers, and visitors.This study seeks to augment the discourse in the field by demonstrating the practical application of key therapeutic garden design principles in a specific context and how these principles impacted the design process.